2020
DOI: 10.1021/acs.jpcc.0c07228
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Space Charge at Metal/Oxide Interfaces in Proton Ceramic Electrochemical Cells

Abstract: The contact potential and the resulting charge accumulation or depletion at the electrode/electrolyte interface are investigated for Ni and Cu group metals in contact with the stateof-the-art proton conductor acceptor-doped BaZrO 3 by firstprinciples calculations and thermodynamic modeling. The contact potential depends on the metal's work function and the defect chemical properties of the oxide, rendering it strongly temperature and atmosphere dependent. Above 900 K, most metals yield negative contact potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Later on, Chen et al systematically explored the impact of space charge on hydration kinetics and electrode kinetics at the Pt/BZY interface. They found that the protons generated from the hydrogen oxidation reaction can be depleted at the Pt/BZY interface similar to the proton depletion at the grain boundary, further deteriorating the surface hydration and subsequently the proton migration of BZY. , The aim of this work is to put forward possible solutions for manipulating the surface space charge of BZY by investigating the influence of surface defects on the proton transport properties of BZY. Specifically, the plasma treatment, which is commonly used to modify nanomaterials for the applications of renewable energy in a clean and efficient way, was originally applied in this work to prepare BZY thin films with various surface defects.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Chen et al systematically explored the impact of space charge on hydration kinetics and electrode kinetics at the Pt/BZY interface. They found that the protons generated from the hydrogen oxidation reaction can be depleted at the Pt/BZY interface similar to the proton depletion at the grain boundary, further deteriorating the surface hydration and subsequently the proton migration of BZY. , The aim of this work is to put forward possible solutions for manipulating the surface space charge of BZY by investigating the influence of surface defects on the proton transport properties of BZY. Specifically, the plasma treatment, which is commonly used to modify nanomaterials for the applications of renewable energy in a clean and efficient way, was originally applied in this work to prepare BZY thin films with various surface defects.…”
Section: Introductionmentioning
confidence: 99%